2003
DOI: 10.1086/377710
|View full text |Cite
|
Sign up to set email alerts
|

A Relation between Supermassive Black Hole Mass and Quasar Metallicity?

Abstract: We analyze spectra for a large sample of 578 active galactic nuclei to examine the relationships between broad emission line properties and central supermassive black hole (SMBH) mass. We estimate SMBH masses by applying the virial theorem to the C iv 1549 broad emission line. Although the FWHMs of C iv and H appear nearly unrelated in individual objects, these FWHMs are well correlated when averaged over subsamples in our database. Therefore, the lines are equally valid indicators of the average SMBH mass in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
115
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(134 citation statements)
references
References 79 publications
18
115
1
Order By: Relevance
“…Table 1 of Baskin & Laor (2005) Baskin & Laor (2005) caution against the use of the C iv emission line for estimating black hole masses through mass scaling relationships of the type derived in this paper. As their conclusion was contrary to that reached in Paper I and by Warner et al (2003) and Vestergaard (2004), we felt that is was important for us to examine the same data as Baskin & Laor (2005) and attempt to understand the origin of these different results.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Table 1 of Baskin & Laor (2005) Baskin & Laor (2005) caution against the use of the C iv emission line for estimating black hole masses through mass scaling relationships of the type derived in this paper. As their conclusion was contrary to that reached in Paper I and by Warner et al (2003) and Vestergaard (2004), we felt that is was important for us to examine the same data as Baskin & Laor (2005) and attempt to understand the origin of these different results.…”
Section: Discussionmentioning
confidence: 65%
“…[7]), as argued in Paper I and by Warner et al (2003) and Vestergaard (2004). It has been argued, however, that C iv may be an inappropriate choice for this application on the grounds that the dynamics of the C iv-emitting gas may not be determined primarily by gravitation; in particular, it has been suggested that (1) the line profiles might be affected by obscuration within the line-emitting region and (2) there are reasons to believe that a significant fraction of the C iv line arises in an outflowing wind.…”
Section: Discussionmentioning
confidence: 67%
“…Significant progress has been achieved over the last years with the calibration of the R-L relation (Vestergaard 2002(Vestergaard , 2009Corbett et al 2003;Warner et al 2003;Peterson et al 2004;Vestergaard & Peterson 2006).…”
Section: Black Hole Mass and Eddington Ratiomentioning
confidence: 99%
“…We analyzed these quasar spectra using a multi-component fit approach (power-law continuum, FeII emission, Balmer continuum emission). We applied the equations given by Kaspi et al (2000), McLure & Jarvis (2002), Vestergaard (2002), and Warner et al (2003) to estimate the black hole mass and to compare, for the first time, results based on CIV, MgII, and Hβ. While CIV is a high-ionization line, Hβ and MgII are low-ionization lines but it can be assumed that the low and high ionization broad line gas are in gravitationally dominated motion (Onken & Peterson 2002).…”
Section: Resultsmentioning
confidence: 99%